2017
DOI: 10.1016/j.ajo.2017.03.032
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Repeat Culture in Fungal Corneal Ulcer Management: A Secondary Analysis of the MUTT-I Randomized Clinical Trial

Abstract: PURPOSE To determine whether patients who had a positive repeated culture was predictive of worse clinical outcome than those who achieved microbiological cure at 6 days in the Mycotic Ulcer Treatment Trial I (MUTT-I). DESIGN Secondary analysis from a multicenter, double-masked, randomized clinical trial. METHODS Setting Multiple hospital sites of the Aravind Eye Care System, India. Study Population Patients with culture-positive filamentous fungal ulcers and visual acuity of 20/40 to 20/400 re-examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…9 Repeat culture positivity despite appropriate antifungal therapy has been correlated with poor clinical outcomes in fungal keratitis, such as worse visual acuity and larger scar size. 5 Therefore, the high rate of culture positivity in our series, combined with the fact that these patients were treated with maximum medical therapy (both topical natamycin and voriconazole, with roughly half randomized to oral voriconazole), underscores the importance of evaluating other potential therapies such as corneal cross-linking or early TPK. 10 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…9 Repeat culture positivity despite appropriate antifungal therapy has been correlated with poor clinical outcomes in fungal keratitis, such as worse visual acuity and larger scar size. 5 Therefore, the high rate of culture positivity in our series, combined with the fact that these patients were treated with maximum medical therapy (both topical natamycin and voriconazole, with roughly half randomized to oral voriconazole), underscores the importance of evaluating other potential therapies such as corneal cross-linking or early TPK. 10 …”
Section: Discussionmentioning
confidence: 89%
“…57 Here, we compare the TPK button culture results by treatment arm to determine if we can detect a benefit of oral voriconazole microbiologically that we were unable to determine clinically.…”
mentioning
confidence: 99%
“…2 The MUTT 1 trial conducted in South India concluded that natamycin is associated with better clinical and microbiological outcomes than voriconazole (VCZ) in smear-positive filamentous fungal keratitis, especially in Fusarium cases. Moreover, Prajna et al 3 commented that the difference in efficacy noted in this trial was primarily attributable to cases caused by Fusarium species. 3 However, studies conducted in North India with Aspergillus as the most common species isolated showed a beneficial effect of VCZ oral or intrastromal with a success rate as high as 80% in cases of recalcitrant fungal keratitis.…”
mentioning
confidence: 79%
“…Moreover, Prajna et al 3 commented that the difference in efficacy noted in this trial was primarily attributable to cases caused by Fusarium species. 3 However, studies conducted in North India with Aspergillus as the most common species isolated showed a beneficial effect of VCZ oral or intrastromal with a success rate as high as 80% in cases of recalcitrant fungal keratitis. 4 Thus, the results of this study may be explained by the difference in the microbiological profile and cannot be generalized for all geographic areas.…”
mentioning
confidence: 79%
See 1 more Smart Citation